Analisis Nilai Sun Protection Factor Krim Tabir Surya Ekstrak Tanaman Gonda (Sphenoclea zeylanica Gaertner) dengan Metode Spektrofotometri UV-Vis - Wintariani, Ni Putu; Lionita, Ni Kadek Vinka (Jurnal Ilmiah Medicamento, 2023)
Free radicals are unstable atoms that can damage cells, causing disease and aging of the skin. Ultraviolet rays cause skin to darken and wrinkle as free radicals produce excess melanin. One of the anti-radical substances is found in the Gonda plant (Sphenoclea zeylanica Gaertner). The plant extract is made into a sunscreen cream dosage form to protect the skin from the dangers of free radicals from sunlight. The aim of this study was to determine the compounds contained in Gonda plant extract and the SPF value of Gonda plant extract sunscreen cream by in vitro method using UV-Vis spectrophotometry. The results showed that Gonda plant extract contains flavonoids, saponins, tannins, steroids, and alkaloids. The SPF value of the cream with 4 concentrations of Gonda plant extract in the formula, namely cream base (0%), F1 (5%), F2 (10%) and F3 (15%) showed the protection category of "none" (1.510), "maximum" (13.488), "ultra" (20.129) and "ultra" (22.921), respectively. The SPF values of the creams of the four formulas were significantly different (p<0.05), and there was a significant (p<0.001) and strong relationship between extract concentration and SPF value. Gonda plant extract cream had SPF value with maximum protection level at 5% concentration and ultra at 10% and 15% concentration. There was a significant and strong relationship between extract concentration and SPF of the cream.